A) 81^-0,75+(1/125)^1/3 -(1/32)^1/3 б) 27^2/3 +(1/16)^-0,75-25^0,5

A) 81^-0,75+(1/125)^1/3 -(1/32)^1/3 б) 27^2/3 +(1/16)^-0,75-25^0,5
Гость
Ответ(ы) на вопрос:
Гость
Давай сделаем по частям, по кусочкам и будет понятно. а) 81 = 3^4 81^-0,75 = (3^4)^-0,75= 3^(4·(-0,75))= 3^-3 = 1/27      125 = 5^3 (1/5^3)^1/3= 1/5^(3·1/3) = 1/5        32 = 2^5 1/(2^5)1/5= 1/2 Сам пример: 1/27 + 1/5 - 1/2 = 10/270 + 54/270 - 135/270 = -71/270 б) 27= 3^3 27^2/3 = (3^3)^2/3= 3^(3·2/3) = 3^2 = 9       16= 2^4 1/16^-0,75 = 1/(2^4)^-0,75 = 1/2^(4·(-0,75))=1/2^3= 1/8          25^0,5= (5^2)^0,5 = 5^(2·0,5) = 5 Сам пример: 9 + 1/8 - 5 = 4 1/8
Не нашли ответ?
Ответить на вопрос
Похожие вопросы